What a dog knows - Wilson, Susan, 1951- (St. Martin's Press, 2021)
"From New York Times bestselling author Susan Wilson comes What a Dog Knows, another heartwarming novel about humans and the dogs that change our lives. Ruby Heartwood has always lived a life on the move. As a traveling psychic, she makes her living working at carnivals and festivals and circuses around New England. It's a life Ruby has made peace with-settling in one place has never been for her. She needs no one, and no one needs her. Until one night, when she is camped by the side of the road in her trusty Volkswagon "Westie" van, a fierce thunder and lightning storm erupts. In the middle of the downpour, she hears a distinct voice telling her to "let me in." In jumps a little black and white dog, and to Ruby's astonishment, she can hear the dog's thoughts. Has she been struck by lightning? Did the storm do this? Is she losing her mind? It turns out, Ruby can hear many dogs' thoughts. She decides to set up semi-permanent residency in the town of Harmony Farms, until she can sort out what is going on, and who the little dog, Hitch, belongs to. But some people in Harmony Farms don't want her there. And it seems that events keep preventing Ruby from leaving. What secrets is this town keeping? Why was she meant to find this dog? And what has Ruby really been running from, all these years?"--